Kaip anglai ir amerikiečiai suvokia lietuvių kalbos priebalsių junginius - Strimaitienė, Marija (Kalbotyra, 1998)
At Vilnius University was carried out an auditory experiment to find out whether Englishmen and Americans distinguish consonant clusters characteristic only of Lithuanian. The experiment showed that the auditors interpreted Lithuanian clusters using their native consonant sequences. The group of Englishmen who could understand Russian distinguished the clusters better than the Americans.